The Influence Of Education Level, Learning Supervision, Work Climate, Work Enthusiasm, Principal's Managerial Ability And Work Ethic On Madrasah Aliyah Negeri 1 Muara Enim Teachers' Work Performance - Abdul Nur Al Islami; Abdul Hamid; Yusnawati Yusnawati (Penerbit Jurnal Indonesia, 2023)
The author conducted research with the aim of knowing and analyzing the effect of education level, learning supervision, work climate, work enthusiasm, managerial ability of the principal and work ethic individually and collectively on the work performance of teachers at Madrasah Aliyah Negeri 1 Muara Enim. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial test simultaneous test and the coefficient of determination. The results showed that the level of education had a significant effect on the work performance of Muara Enim 1 Madrasah Aliyah Negeri 1 teachers. Learning Supervision has a significant effect on achievement. Work climate has a significant effect on work performance. Morale has a significant effect on work performance. The Principal's Managerial Ability has a significant effect on work performance. Work Ethics has a significant effect on work performance. Level of education, supervision of learning, work climate, morale, managerial ability of the principal and work ethic have a significant effect on the work performance of Madrasah Aliyah Negeri 1 Muara Enim teachers.